Plants metabolites as a prospective approach against the COVID-19 - Noor, Aijaz Ul; Aziz, Ruqaya (International Journal of Basic & Clinical Pharmacology, 2021)
The Coronavirus disease 2019 (COVID-19) caused by an RNA virus SARS-CoV-2 is an emerging global health pandemic. With currently no approved treatment or prophylaxis, the SARS-CoV-2 is rapidly transmitted via touch, droplets, and fomites. In most affected patients, the disease will have mild flu-like symptoms (fever, dry cough, and difficulty in breathing) and in selected patients may cause severe complications such as progressive pneumonia, acute respiratory distress syndrome, and organ failure due to hyper-inflammation and cytokine storm syndrome. Understanding the pathogenesis of the disease is essential for identification and rational design of effective drug targets. The plant metabolites can provide as a prospective approach for SARS-CoV-2, due to lowest possible side effect and antiviral properties. In this report, we provide an overview of the disease pathogenesis and highlight the potential therapeutic interventions.